Law as Gift at the Basis of "Humanae vitae" and "Veritatis splendor" - Smith, Janet E. (Scripta theologica, 2018)
Many believed that Veritatis splendor (now 25 years old) was written to defend Humanae vitae (now 50 years old). It is certainly true that the dissent from HV was the impetus for the development of the now abandoned moral system of proportionalism, which was the impetus for Veritatis splendor . Veritatis splendor sought to refute the claim of proportionalism that there are no universal objective absolute moral norms. This essay focuses on another important feature of «law» shared by Veritatis splendor and Humanae vitae : the view that law is a gift from God and something that deserves obedience since abiding by it is a means for human beings to achieve true freedom and to fulfill their nature.